Extraction and characterization of microfibrillated cellulose (MFC) from Rhododendron ponticum isolated using cryocrush pre-treatment and its potential for mycelium cultivation - de M. de Lima, Tielidy A.; de Lima, Gabriel Goetten [UNESP]; Rouxel, Pierre; Bezerra, Gilberto Silva Nunes; Fehrenbach, Gustavo W.; Magalhães, Washington L.E.; Nugent, Michael J.D. (Elsevier, 2024)
Rhododendron ponticum (R. ponticum), a rapidly spreading invasive species in Ireland, was investigated for its potential use in creating sustainable bioproducts. This study explored the utilization of R. ponticum biomass as a source of microfibrillated cellulose (MFC) for fungal cultivation. The production of MFC was evaluated employing a novel cryocrushing treatment combined with a twin-screw extruder (TSE). The results demonstrated a significant increase in film strength, up to 332.3 MPa, with increasing TSE steps compared to 72.5 MPa in untreated samples. X-ray diffraction (XRD) analysis revealed a decrease in crystallinity from 68.93 % to 59.2 %, following cryocrushing and TSE treatment. Additionally, MFC subjected to the highest TSE treatment (12 steps) was successfully used as a substrate for cultivating Agaricus blazei mushrooms using 0.2 wt%, 0.5 wt%, and 1 wt% MFC over a period of 7 days. Fourier-transform infrared spectroscopy (FTIR) confirmed the presence of chitin/chitin glucan within the fungal fibers. This research highlights the potential for transforming the invasive R. ponticum into valuable biocomposite materials. These MFC-fungus composites hold promise for various applications, including sustainable packaging, biodegradable plastics, and eco-friendly textiles.
Keywords: Cryocrush; Fungal cultivation; Natural fibers